The Victims of Victims: Islamophobia in the South Korean Feminist Movement - Muquita, Namira Risqi Putri (Islamic Studies Review, 2024)
This research attempts to introduce a new perspective on the complex relationships in South Korea's patriarchal society that produces "victims of victims". The patriarchal culture in South Korea stems from Confucian values that have demeaned women by branding them immoral (hwanyang-nyeon/화냥년). In modern times, these Confucian values perpetuate misogyny and create a second-class identity for women in South Korean society. Thus, the feminism movement was born as a form of emancipation to fight the enduring injustice against women in South Korea. By using Jürgen Habermas' perspective on moral discourse and Spinner-Halev’s perspective on enduring injustice, this study aims to examine the formation of a victim mentality in South Korean women and its relationship with the label of 'patriarchy' pinned on Islam, which then contributes to intensified Islamophobia in South Korea. The construction of Islam as patriarchal and degrading to women is often expressed alongside acts of racism and xenophobia. This phenomenon constitutes a vicious cycle. Deep-seated trauma and hatred due to mistreatment and othering experiences over time has caused women in South Korea to internalize a victim identity. Ironically, this creates new victims through anti-Islamic campaigns in the feminist movement. By conducting a literature review, this research seeks to analyze the relationship between enduring injustice due to patriarchal culture, mental formation of victims and Islamophobia in the South Korean feminist movement.